Impact of COVID-19 pandemic on outcome of acute appendicitis: a retrospective analysis - Patil, Linganagouda S.; Jagadeesha, Reena (International Surgery Journal, 2021)
Background: Acute appendicitis is the most common abdominal surgical emergency. Lockdown and stay-at-home orders are strategies that were implemented globally during the acute pandemic period of COVID-19 to prevent disease dissemination, health system overload and mortality. However, there are concerns that patients did not seek necessary health care because of these rules. Methods: Retrospective observational study was conducted on patients who presented with acute appendicitis from January 2020 to May 2020. They were classified according to the time of presentation that is before declaration of the state of alarm (pre-COVID-19), and after its declaration (post-COVID-19) in India (24 March 2020). An evaluation was made of demographic variables, complications and duration of hospital stay in both the groups. Results: 45 patients were included, 20 in pre-COVID-19 group and 25 in post-COVID-19 group. In post-COVID-19 group, the interval from onset of symptoms to admission was 65.0 hour, which is significantly longer than the 17.3 hour interval noted in pre-COVID-19 group (p<0.001). The prevalence of complicated appendicitis after the epidemic outbreak was significantly higher than before the outbreak (52% versus 20%, p<0.001).The mean hospital stay was longer in post-COVID-19 group (5.6±5.9 versus 3.2±4.3 days; p=0.041). Conclusions: COVID-19 pandemic influenced the time of diagnosis of appendicitis, as well as its course, and mean hospital stay. Complicated appendicitis was more common in patients with acute appendicitis after the outbreak of COVID-19 pandemic.